Istiqra Al Ma'nawiy's Reasoning: As a Model of Indigenzation and Contextualization of Islamic Law (Hazairin and Hasbi Ash Shiddiqiy's Thought) - Tabroni, Imam (TSAQAFAH, 2024)
This article highlight the background and the growth of American Muslim with their need of Character Education. As the super power nation, American culture of education rest on secular and multicultural social system and society. Become the minority, the growth of muslim in American may face several constraint as prejudice and other, then they began predicted to be alienated – especially after 9/11. But I analyze the good action and morality performed by several american muslim public figures which attract and spread the peace as very message of Islam. This literature review seek the publications and works published concerning the Islam and Character Education in America. I also reflect on several facts with al-Attas perspective on Islamization with comparing its phenomena in Indonesian sense of character education. This study found the good prospect of educational institution and character education activities, beside the increase of private islamic schools caused by the culture of Western-American society.